PENGARUH KOMPETENSI, DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KEPALA SEKOLAH DASAR SE KABUPATEN BIREUEN - Hibban, Ibnu; Yusuf, M. (LPPM-UNIKI, 2021)
This study aims to examine, 1) the effect of competence on the principal's performance, 2) the influence of work discipline on the principal's performance, 3) the effect of work experience on the principal's performance, and 4) the influence of competence, work discipline and work experience on the principal's performance. SD in Bireuen Regency. The research method used in this study is the associative method with a quantitative approach, to 147 elementary school principals throughout Bireuen Regency, with the collection technique using a closed questionnaire instrument. The analytical method used is a path analysis approach. The results showed that 1) There was a significant influence of the Competency factor on the Principal's Performance, amounting to 8.45%. 2) It is statistically proven that the work discipline factor affects the Principal's Performance by 12.69%. 3) It is statistically proven that the work experience factor affects the principal's performance, amounting to 7.82%. 4) The results of the correlation coefficient between competence, work discipline and work experience on the principal's performance obtained R of 0.638 explaining the relationship between competence, work discipline, and work experience on performance, has a fairly high level of relationship, and is linearly related, with the degree of relationship of 0.638. The value of the coefficient of determination of 0.407 explains that the contribution of competence, work discipline, and work experience to the Principal's Performance is 40.7%. While the rest (residual value) of the role of the variables that were not studied was 59.3%. The residual value shows that there are other factors that can affect the performance of school principals throughout Bireuen Regency, such as organizational climate, work facilities, education and training, and others